2014
DOI: 10.1095/biolreprod.113.115790
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Receptor NR2F2 Activates Star Expression and Steroidogenesis in Mouse MA-10 and MLTC-1 Leydig Cells1

Abstract: Testosterone production is dependent on cholesterol transport within the mitochondrial matrix, an essential step mediated by a protein complex containing the steroidogenic acute regulatory (STAR) protein. In steroidogenic Leydig cells, Star expression is hormonally regulated and involves several transcription factors. NR2F2 (COUP-TFII) is an orphan nuclear receptor that plays critical roles in cell differentiation and lineage determination. Conditional NR2F2 knockout prior to puberty leads to male infertility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 74 publications
4
60
0
Order By: Relevance
“…The Ϫ131/Ϫ54-bp region is rich in transcription factor binding sites, including elements for SF1, AP1, NUR77, GATA4, and COUP-TFII (4,31,34,46). Mutation of several of these binding sites (COUP-TF, NUR77/SF1, and GATA) in the context of the Ϫ131-bp Star reporter (that no longer harbor the MEF2 element) impaired the MEF2/cAMP cooperation.…”
Section: Mechanisms Of Mef2 Action On the Star Promotermentioning
confidence: 99%
“…The Ϫ131/Ϫ54-bp region is rich in transcription factor binding sites, including elements for SF1, AP1, NUR77, GATA4, and COUP-TFII (4,31,34,46). Mutation of several of these binding sites (COUP-TF, NUR77/SF1, and GATA) in the context of the Ϫ131-bp Star reporter (that no longer harbor the MEF2 element) impaired the MEF2/cAMP cooperation.…”
Section: Mechanisms Of Mef2 Action On the Star Promotermentioning
confidence: 99%
“…In the testis, we [8,9] and others [11,119] found that COUP-TFII is expressed in some peritubular myoid cells and in Leydig stem cells giving rise to ALC. Because Coup-tfii À/À mice die before E10.5, an inducible inactivation strategy was used and revealed that COUP-TFII is essential for progenitor Leydig cell formation and their further maturation into functional adult Leydig cells [119].…”
Section: Transcriptional Regulators Of Leydig Cell Differentiationmentioning
confidence: 77%
“…FLC stem cells start to differentiate and gradually acquire the ability to synthesize androgens required for masculinization of the foetus [6] before disappearing after birth. The ALC population is derived from undifferentiated spindle-shaped, fibroblast-like mesenchymal Leydig stem cells that are believed to be present during fetal life [8][9][10][11]. The source of these cells has been identified as peritubular, interstitial, and/or peri-vascular in mouse and human testes [10][11][12].…”
Section: Origin and Function Of Leydig Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the transcription factors myocyte enhancer factor 2 (MEF2) and chicken ovalbumin upstream promoter‐transcription factor II (NR2F2, COUP‐TFII) were identified in the mouse testis, including Leydig cells (Qin et al ., ; Daems et al ., ; Mendoza‐Villarroel et al ., ,b). The MEF2 family of transcription factors contains four members: MEF2A, 2B, 2C and 2D.…”
Section: Introductionmentioning
confidence: 99%